Rheological and quality characteristics of composite gluten-free dough and biscuits supplemented with fermented and unfermented Agaricus bisporus polysaccharide flour. (15th January 2019) - Sulieman, Abdellatief A.; Zhu, Ke-Xue; Peng, Wei; Hassan, Hayat A.; Obadi, Mohammed; Siddeeg, Azhari; Zhou, Hui-Ming
Graphical abstract: Highlights: Novel CGF biscuits were prepared by added FABP flour and UABP flour. Rheological properties were improved by both FABP flour and UABP flour. An increase of fibers, amino acids and minerals of CGF biscuits was observed. Physical and sensorial properties were enhanced by added polysaccharide flours. Abstract: In this study, functional, rheological and physicochemical characteristics were carried out for composite gluten-free (CGF) flours, dough and biscuits, respectively fortified with fermented and unfermented Agaricus bisporus polysaccharide (FABP and UABP) flours. Addition of both FABP flour and UABP flour improved functional properties, while addition of FABP flour decreased viscosity property. Incorporation of both polysaccharide flours in CGF biscuit dough revealed a significant increase in rheological moduli (G′ and G″) and a decrease in tan (δ). Supplementation of UABP flour increased thickness, whereas supplementation of FABP flour increased diameter and spread ratio. All CGF biscuit formulations exhibited lower fracture strength and hardness compared to the control. Furthermore, both UABP flour and FABP flour formulation (F3 ) contained the highest nutrients in terms of protein, dietary fibers, amino acids and minerals among the CGF biscuit formulations. The sensory evaluation result showed that FABP flour formulation (F1 ) and UABP flour F1 were most acceptable.